건설공사 사후평가시스템 입력오류 분석에 관한 연구 - 김경훈; 이두헌; 김태영; Kim, Kyong-Hoon; Lee, Du-Heon; Kim, Tae-Yeong (한국건설관리학회 논문집, 16(2), 2015)
The data are often missed and many errors of the data are generated in the input process for the post evaluation system on the construction projects, and the reliability of the data falls down much. Accordingly, the detailed analysis about missing and error of data was conducted to ensure reliability of the analysis results about post evaluation on the construction projects. As results in this study, a lot of input data were missed at the initial construction phase, and the data errors were found in the inaccuracy of reference reports, the lack of understanding about input data, and the failure of KRW unit. 현재 건설공사 사후평가시스템 입력과정에서 자료가 오류 및 누락이 발생되는 경우가 많아 데이터의 신뢰성이 떨어지는 경우가 많다. 이에 따라 본 연구에서는 사후평가 결과분석의 신뢰성 확보를 위해 건설공사 사후평가시스템의 입력누락 및 입력오류에 대한 세부적인 분석을 실시하였다. 분석결과, 건설사업 초기 단계일수록 자료의 미입력된 자료의 비중이 높게 나타났다. 그리고 분석된 등록오류로는 참고자료의 부정확, "원" 단위 오류, 입력항목에 대한 이해부족 등으로 나타났다.